Mechanisms of chromium (VI) resistance by acinetobacter haemolyticus [electronic resource] - 302204 Quek, Hsiao Pei; Fakulti Sains (2009)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2009